Micrographic View of Graft Union Formation Between Watermelon Scion and Squash Rootstock - Devi, Pinki; DeVetter, Lisa; Kraft, Michael; Shrestha, Srijana; Miles, Carol (Frontiers in Plant Science, 2022)
Grafting has become a common practice for watermelon (Citrullus lanatus) production in many parts of the world, due to its efficacy against biotic and abiotic stressors. However, grafting success for watermelon is challenging in part due to the complex anatomy of the cucurbit vascular system. The survival of grafted transplants depends on compatibility between the scion and rootstock, which in turn depends on anatomical, physiological, and genetic variables. A better understanding of cucurbit anatomy and graft union formation would inform grafting approaches and transplant management. An anatomical study was conducted by scanning electron microscopy (SEM) at 11 and 25 days after grafting (DAG) with seedless watermelon cultivar Secretariat grafted onto compatible rootstock cultivars Pelop (Lagenaria siceraria) and Tetsukabuto (Cucurbita maxima x C. moschata) in comparison to nongrafted watermelon and rootstocks seedlings. At 11 DAG, the parenchymatic cells of the central pith of grafted plants were dead and a necrotic layer was observed, representing the beginning of callus formation. New xylem strands were formed in the vascular system, connecting the rootstock with the scion. At 25 DAG, fully developed vascular bundles at the graft interface were observed with both scion-rootstock combinations. Although more studies are necessary to characterize the sequence of physiological events after grafting in Cucurbit species, this study is one of the first to describe the complex anatomical changes that occur during watermelon grafting.